(untitled) (Journal of Engineering, 2003)
This paper presents a procedure for the free vibration analysis of stiffened conical shell by the finite element method. The element used is a modified eight-node superparametric shell element. The effects of the number and cross-section area of stiffeners on the conical shells were analyzed. The results showed that increasing the number of stiffeners and their cross-’i’ectional area tend to increase the natural frequency of the conical shell. These results are iompared with available research results and those obtained from MSC.